Liberal peace transitions : between statebuilding and peacebuilding - Richmond, Oliver P. (Edinburgh University Press, 2009)
This book examines the nature of 'liberal peace': the common aim of the international community's approach to post-conflict statebuilding. Adopting a particularly critical stance on this one-size-fits-all paradigm, it explores the process by breaking down liberal peace theory into its constituent parts: democratisation, free market reform and development, human rights, civil society, and the rule of law. Readers are provided with critically and theoretically informed empirical access to the 'technology' of the liberal peacebuilding process, particularly in regard to Cambodia, Kosovo, East Timor, Bosnia and the Middle East. Key Features critically interrogates the theory, experience, and current outcomes of liberal peacebuilding includes five empirically-informed case studies: Cambodia, Kosovo, East Timor, Bosnia and the Middle East focuses on the key institutional aspects of liberal peacebuilding and key international actors assesses the local outcomes of liberal peacebuilding